Enhancing Self-determination in Children with Autism via Behavioural Interventions - RAMEY, DEVON MICHELLE (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2019)
Individuals with autism spectrum disorder (ASD) are thought to experience a much lower quality of life (QoL) than the general population across the lifespan. Emotional well-being (i.e., happiness) is considered one of the main indicators of QoL, but there are challenges with measuring this construct among children with ASD. Due to the social and communication deficits inherent to the condition, children with ASD are typically unable to self-report their own degree of happiness. As happiness is a covert behaviour that cannot be directly observed, practitioners must rely on the observable behaviours theorised to be associated with happiness instead. These overt indicators of mood are referred to as indices of happiness (or unhappiness), and the current research established that these mood indices can be operationally defined and reliably measured in young children with ASD. The main purpose of this research programme was to measure these indices of happiness and unhappiness as an outcome of a self-determination-based intervention designed to improve the QoL of children with ASD. Self-determination is a key component of QoL and it can be defined as the ability to exercise control over one?s own life, without undue influence from others. Self-determination develops autonomy, which in turn, improves the overall QoL of an individual. Choice-making is considered necessary for self-determination. By providing children with ASD with choice-making opportunities, practitioners can promote their self-determination and overall QoL. This research demonstrated that the provision of a choice intervention package, which included three different types of choice, was effective for improving the mood and self-determination of young children with ASD. As a result of this intervention, it was theorised that the overall QoL of these children was enhanced. The findings from this research are discussed in terms of clinical recommendations and implications for future research.
APPROVED
Keywords: autism; happiness; mood; choice; intervention; quality of life